Rapidly developing large pneumatocele and spontaneous pneumothorax in SARS-CoV-2 infection - Sanivarapu, Raghavendra R. (Respir Med Case Rep, 2020)
Coronavirus disease 2019 (COVID-19) has spread to more than 70 countries around the world since its discovery in 2019. More than 2.5 million cases and more than 130,000 deaths have been reported in the United States alone. The common radiological presentation in this disease is noted to be the presence of ground glass opacities and/or consolidations. We report a case of 40-year-old male admitted for COVID-19 and rapidly deteriorated into severe acute respiratory distress syndrome requiring intubation and mechanical ventilation with no prior history of smoking or lung disease. The patient had normal imaging 3 days prior to admission to the hospital and rapidly developed a large pneumatocele with pneumothorax requiring chest tube placement that later on resolved. This is a unique radiologic finding in COVID-19 and likely related to severe inflammation secondary to SARS-CoV-2 infection.